Design and Synthesis of New Pyrazole‐Based Heterotricycles and their Derivatization by Automated Library Synthesis. (8th June 2020) - Fricero, Prisca; Bialy, Laurent; Czechtizky, Werngard; Méndez, María; Harrity, Joseph P. A.
Abstract: Small‐molecule heterocycles bearing orthogonal functionality have the potential to deliver diverse structural motifs that aid the drug‐discovery effort. This work highlights how a readily assembled N ‐hydroxyethyl pyrazole trifluoroborate offers rapid access to architecturally distinct 5‐6‐6‐ and 5‐7‐6‐fused tricyclic compounds. This chemistry is not only amenable to single compound synthesis, but also to high‐throughput experimentation. It gives easy access to diverse compound arrays with various physicochemical and ADME profiles by fully automated library synthesis. The combination of the high‐throughput experimentation with rapid testing of the compounds in an integrated physicochemical and ADME profiling workflow allows accelerated design of novel lead compounds in drug‐discovery projects. Abstract : Taking shape : A readily accessible bifunctional pyrazole can easily be elaborated to architecturally distinct 5‐6‐6‐ and 5‐7‐6‐fused tricyclic compounds. These have been further modified to form new compound libraries bearing a broad range of physicochemical and eADME properties.